2017
DOI: 10.1155/2017/3145946
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Distribution in Pulp and Seeds of Black and Red Goji Berries as Affected by Boiling Processing

Abstract: Pulp and seeds from four varieties of black goji and two varieties of red goji with different geographical origins were examined for their total phenolic content (TPC), total flavonoid content (TFC), condensed tannin content (CTT), monomeric anthocyanin content (MAC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity, and ferric reducing antioxidant power (FRAP) using colorimetric methods. Contribution rates of pulp and seed to phytochemical contents and overall antioxidant capacities of whole fruits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Zhang, Chen, Zhao, and Xi () determined the total phenolic levels of eight Chinese native goji berry genotypes ranged from 26.9 to 73.4 mg GAE/g. Another study showed that total phenolic content of black and red goji berry pulp ranged from 3.44 to 6.45 mg GAE/g and 3.45 to 3.47 mg GAE/g, respectively (Xin, Zhu, Du, & Xu, ). In our study, black goji berry infusion had higher amount of phenolic compounds than red goji berry infusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang, Chen, Zhao, and Xi () determined the total phenolic levels of eight Chinese native goji berry genotypes ranged from 26.9 to 73.4 mg GAE/g. Another study showed that total phenolic content of black and red goji berry pulp ranged from 3.44 to 6.45 mg GAE/g and 3.45 to 3.47 mg GAE/g, respectively (Xin, Zhu, Du, & Xu, ). In our study, black goji berry infusion had higher amount of phenolic compounds than red goji berry infusion.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al () reported DPPH free radical scavenging activities of extracts from fruits of the goji berry genotypes ranged from 36 to 85 µmol TE/g fresh weight. Xin et al () determined antioxidant activity of black and red goji berry pulp by DPPH assay as between 63.09–85.15% and 44.63–47.63%, respectively. The antioxidant activities measured at 11th day of storage of kombucha samples was increased to 100.70 ± 0.00 , 97.68 ± 0.62 , and 99.54 ± 0.29 µmol Trolox/g t.s.s, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycium ruthenicum Murr . fruits (LRM, “Hei Guo Gou Gi” in Chinese or called “black goji berry”) (Xin, Zhu, Du, & Xu, ) are known to be a good source of functional components including polysaccharides, phenolic compounds, anthocyanins, fatty acids, and minerals (Peng et al, ). Among these chemical constituents, anthocyanins and polysaccharides have been proven to be the major bioactive compounds (Qian, Zhao, Yang, & Huang, ), with anthocyanins, the main functional compositions in these berries (Islam, Yu, Badwal, & Xu, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is a large content of purple pigment (up to 3.88 mg/g in fresh fruits), which is a rare edible natural anthocyanin resource. It is expected to become a colorant for cosmetics, pharmaceuticals, beverages, and food [2]. In addition, it contains a variety of trace elements, confirming good medicinal plant resources.…”
Section: Introductionmentioning
confidence: 99%